Impacts of prescribed fire on soil loss and soil quality: An assessment based on an experimentally-burned catchment in central Portugal - Emilia Urbanek (CATENA, 2013)
Hillslope-scale losses of soil, organic matter and selected nutrients pre- and post-prescribed fire in the shrub-vegetated Vale Torto catchment with thin stony soil in central Portugal. The soil erosion results are compared with measurements: (1) on a nearby hillslope burned by wildfire and monitored at the hillslope scale; and (2) on long-unburned terrain at small-plot, hillslope- and catchment-scales. Hillslope-scale pre- and post-fire soil erosion was recorded over periods of 6 weeks to 5 months for (1) 9.5 months pre-fire and 27 months post-fire in the prescribed fire catchment, and (2) c. 3 years post-fire at the wildfire site. Organic matter content, pH and selected nutrients were measured in the eroded sediment and in pre- and post-prescribed fire surface soil. It is concluded that: (1) both types of fire (prescribed fire and wildfire) caused increased erosion compared with unburned terrain; and (2) the hillslope-scale post-prescribed fire soil losses were higher than many reported smaller-scale post-prescribed fire and post-wildfire erosion rates in the Mediterranean. By comparison, post-fire erosion for both fire types was less than that caused by some other types of common soil disturbance (e.g. types of tillage) and even that on undisturbed scrub in low rainfall areas of the Mediterranean. Total estimated post-prescribed fire particulate losses of organic matter and nutrients represent only 0.2-2.9% of the content in the upper 2 cm of soil, suggesting only a relatively small fire impact on soil quality, although few high-magnitude rainstorms following the fire may be a factor. The longer-term implications for soil conservation of repeated prescribed fire in the Mediterranean are explored and future research needs discussed.